N,N'-bi-(5-methyl-methylsalicylidene)-2,2-dimethylpropane-1, 3-diamine palladium(ii): catalyst for heck reaction - Wan Ibrahim, Wan Nazihah; Shamsuddin, Mustaffa; M. Yamin, Bohari (The Malaysian Analytical Sciences Society (ANALIS), 2007)

(untitled)
A new palladium(II) complex of a Schiff base ligand, â€œN,Nâ€™-bis-(5-methyl-methylsalicylidene)-2,2-dimethylpropane-1,3-diamineâ€? has been synthesized and characterized by analytical and spectroscopic data such as FTIR, 1H and 13C NMR spectroscopy, X-ray crystallography and CHN elemental analysis. The ligand acted as a N,N,O,O tetradentate ligand which the metal is coordinated to the azomethine nitrogen and phenolic oxygen. The palladium complex was tested as catalyst in the Heck reaction of iodobenzene with methyl acrylate in the presence of sodium hydrogen carbonate as base N,N-dimethylacetamide at reflux temperature (120Â°C). The activity of the catalyst was monitored by 1H NMR